ЕЛЕКТРОМАГНІТНІ ПРОЦЕСИ У ТРИФАЗНОМУ ДВОМОСТОВОМУ КОМПЕНСАЦІЙНОМУ ПЕРЕТВОРЮВАЧІ З ОДНІЄЮ КОМУТУЮЧОЮ ЛАНКОЮ - Бойко, В.С. (Інститут електродинаміки НАН України, Київ, 2025)
The results of studies of the energy characteristics of a two-bridge parallel-type compensation converter are presented. The converter is one of the representatives of a new generation of compensation-type devices, the main feature of which is the use of a three-phase group of fully controlled devices (IGBT) in the commutating link. They, together with a three-phase capacitor bank, create a switching link, a converter element that is capable of changing the nature of electromagnetic processes, namely, providing compensation for its own reactive energy, and, if necessary, generating reactive energy into the power supply network. The indicated energy capabilities of the compensation converter under study depend mainly on the value of the angle α and the commutation angle γ. Therefore, the main purpose of the publication is to study the possibilities of changing them by regulating the process of recharging the capacitor battery with using transistors of the commutating link. As a result, it has been proven that, taking into account the peculiarities of the operating modes of the converter during the process of supplying energy to DC consumers, it is possible, by coordinating the angles of regulation and commutating, to achieve high energy efficiency of the operation of the converter. References 6, figures 6.